BIOREMEDIASI LIMBAH MINYAK BUMI DENGAN TEKNIK BIOPILE DI LAPANGAN KLAMONO PAPUA - Munawar, Munawar; Zaidan, Zaidan (Sains & Matematika, 2013)
Research of bioremediation of petroleum waste by indigenous petrophilic bacteria with biopile techniques at Klamono Area in Papua has been done. Petroleum waste was derived from various sources, namely tank cleaning, oil spills, oil catcher, leaking pipes, and drilling wastes containing oil residue. Preparation of petroleum waste has been done by adding wood sawdust as a bulking agent as much as 10% (w/w), the ratio of C: N: P: K = 100:5:1; 0.1 and mixed cultures of indigenous petrophilic bacterial isolated from the sources of the waste that has been collected in a storage-pit that Pseudomonas sp. (PSP01), Pseudomonas sp. (PSP05), and Bacillus sp. (PSP03) with 1:1:1 ratio of 0.5% (v/w). During the bioremediation process was aerated at a rate of 1 liter/jam/m3. Monitoring process have been done every week by doing the sampling with multiple sampling method to determine the five stations and each station has determined three sampling points,namelythe surface, middle and bottom based on the depth, samples have been obtained pooled and analyzed. The results showed that a decline in Total Petroleum Hydrocarbon (TPH) of 91.04% for six weeks. Total bacterial populations during bioremediation processes ranging 103 to 108 CFU/gram of soil. In addition at the end of the observation showed that the toxic aromatic compounds benzene, toluene, ethylbenzene, and xylene (BTEX) showed concentrations under the Environmental Quality Standards. Thus, indigenous petrophilic bacteria effective as biological agents in the bioremediation of petroleum waste by biopile method.